2007
DOI: 10.1254/jphs.sc0070207
|View full text |Cite
|
Sign up to set email alerts
|

Orally-Administered Caspase Inhibitor PF-03491390 Is Retained in the Liver for Prolonged Periods With Low Systemic Exposure, Exerting a Hepatoprotective Effect Against α-Fas-Induced Liver Injury in a Mouse Model

Abstract: Abstract. In a mouse model of α-Fas-induced acute liver injury, the orally-administered caspase inhibitor PF-03491390 (formerly named IDN-6556) was retained in the liver for prolonged periods with a low systemic exposure. Reductions in the elevated plasma levels of alanine aminotransferase (ALT) revealed that the retention of PF-03491390 in the liver exerted a hepatoprotective effect, even when pre-administered to mice 4 h before α-Fas insult. Prolonged retention of PF-03491390 in the liver after oral administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 12 publications
(11 reference statements)
1
16
0
Order By: Relevance
“…Subsequent experiments evaluating possible paracrine effects from emricasan‐treated hepatocytes evidenced a positive crosstalk, leading to marked de‐activation of HSC, together with partial improvements in LSECs and HMϕs. These observations are in agreement with previous works demonstrating the modulation of paracrine effectors in response to pan‐caspase inhibitors . Nevertheless, our study adds a significant piece of knowledge in this process.…”
Section: Discussionsupporting
confidence: 93%
“…Subsequent experiments evaluating possible paracrine effects from emricasan‐treated hepatocytes evidenced a positive crosstalk, leading to marked de‐activation of HSC, together with partial improvements in LSECs and HMϕs. These observations are in agreement with previous works demonstrating the modulation of paracrine effectors in response to pan‐caspase inhibitors . Nevertheless, our study adds a significant piece of knowledge in this process.…”
Section: Discussionsupporting
confidence: 93%
“…SMAC mimetics are the most exciting clinical candidates that have emerged. Conversely, clinical caspase inhibitor Emricasan is a liver-targeted agent (111,112), probably limiting its general utility. New classes of caspase inhibitors (and especially caspase-8-specific molecules) will be undoubtedly very useful.…”
Section: Discussionmentioning
confidence: 99%
“…Emricasan is an irreversible pan-caspase inhibitor that is orally active and retained in the liver 67. Caspases play an important role in apoptosis and it has been demonstrated that steatotic hepatocytes undergo apoptosis 68.…”
Section: Medicationsmentioning
confidence: 99%